UPAYA HUKUM KASASI SECARA ELEKTRONIK (E-COURT) DI PENGADILAN AGAMA RAHA - Azhari, Rizka Anugrah; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
Religious courts are one of the judicial institutions used by Islamic justice seekers to handle certain issues such as marriage, inheritance, wills, waqf grants, shodaqoh, and sharia economics. In accordance with Supreme Court Regulation no. 1 of 2019 concerning electronic case administration, they are now using the e-court application. Therefore, the author wants to learn more about the problem of administering legal remedies and electronic cassation trials, or e-court, in religious courts. The focus of their research is Lawrence M. Friedman's theory of the legal system and how religious courts implement the administration of cassation cases. This study is normative-empirical and qualitative, and the data was collected through literature study. Requests for cassation legal action, payment of court fees, preparation of a deed of cassation request, notification to the respondent regarding legal action, sending memories, counter-memories, inzage, sending files, and revocation are all part of the administration of e-court cassation legal efforts. The network is an obstacle that hinders the use of electronic courts, especially for electronic appeals. They are sometimes unable to upload documents due to unstable network. Thus, the Raha Religious Court established an electronic court center to help people who use the electronic court system if they encounter problems. This e-court system's cassation legal efforts increase the smoothness, convenience and success of users.